Semiconductors, Strategic Vulnerability, and Selective Decoupling: China’s Techno-Nationalist Response to US Restrictions - Sobia Hanif; Bazgha Murtaza (CISS Insight Journal, 2025)
In the contemporary era marked by technological breakthroughs, advanced semiconductors are widely recognized as the “currency of power,” with their control determining geopolitical leverage, national security, and digital supremacy. As the prime assets of modern economic and defence systems, command over high-end chips is redefining the power dynamics of the Twenty-first century. This study aims to investigate China’s unprecedented push for technological self-sufficiency amid perceived vulnerabilities associated with its dependency on foreign sources for microchips and the weaponization of semiconductor value chains by the United States (US). This study examines the national security imperatives that shape states’ behaviour in an anarchic system. Employing the qualitative case study approach, the study aims to investigate the significant ramifications of the US-China semiconductor rivalry for the stability of the global technopolitical and geopolitical order. Additionally, it aims to assess the policy approaches and national security priorities of China related to its techno-nationalist aspirations. The research findings reveal that the technological competition between the US and China is set to grow exponentially in transnational domains.